2017
DOI: 10.1016/j.pdpdt.2016.11.013
|View full text |Cite|
|
Sign up to set email alerts
|

Photoinactivation of single and mixed biofilms of Candida albicans and non-albicans Candida species using Photodithazine®

Abstract: This study evaluated the effectiveness of antimicrobial photodynamic therapy (aPDT) mediated by Photodithazine (PDZ) formulated in hydrogel, in the inactivation of mono and duo-species biofilms of Candida albicans, Candida glabrata and Candida tropicalis. Standardized suspensions of each strain were prepared and after biofilm formation, mono-species were treated with 150 and 175mg/L of PDZ for 20min (pre-irradiation time), and exposed to LED light at a dose of 37.5J/cm (660nm). The duo-species biofilms (C. alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
1
16
0
1
Order By: Relevance
“…The application of aPDT mediated by PDZ at 200 mg l −1 reduced the biomass of the biofilm by 30.9%. These results are in agreement with those found in the literature which observed that the combination of 150 mg l −1 of PDZ associated with LED light produced reductions on total biomass equivalent to 24.4, 39.2 and 43.7% for C. albicans, Candida tropicalis and C. glabrata, respectively (Carmello et al 2017). The total biomass of the biofilms treated with SDT mediated by PDZ was similar to the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The application of aPDT mediated by PDZ at 200 mg l −1 reduced the biomass of the biofilm by 30.9%. These results are in agreement with those found in the literature which observed that the combination of 150 mg l −1 of PDZ associated with LED light produced reductions on total biomass equivalent to 24.4, 39.2 and 43.7% for C. albicans, Candida tropicalis and C. glabrata, respectively (Carmello et al 2017). The total biomass of the biofilms treated with SDT mediated by PDZ was similar to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, when PDZ was applied in the absence of light or US, this PS was not able to reduce the suspension viability of C. albicans. The non-toxicity of PDZ has been reported in the literature (Dovigo et al 2013;Carmello et al 2017). Therefore, the effect of the sensitizers on the C. albicans viability depends on the type of the PS evaluated.…”
Section: Discussionmentioning
confidence: 98%
“…After incubation, the OD 490 was measured by a spectrophotometer (UV-2600; Shimadzu, Japan) to quantify biofilm activity. In addition, the total biomass of the biofilm was quantified by using a previously reported CV assay (40,41). After treatment, the supernatant of the biofilm was removed, the biofilm was washed with PBS four times, fixed with 95% methanol, and stained with 500 l of 0.1% CV at 37°C for 10 min in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary studies indicated antimicrobial PDT activity only for each species individually, but there was no reduction in total biomass of dual species biofilms. 371 Further improvements of the PDZ-Natrosol hydrogel formulation against Candida spp. were studied in vitro and in vivo (case study), showing potential for treatment of denture stomatitis.…”
Section: Chlorinsmentioning
confidence: 99%